Lithostratigraphy, geochemistry, and depositional environments of the Upper Cretaceous succession from the Mezino-Lapshinovka section (Eastern Russian Platform) - S.O. Zorina; L.S. Khabipyanov; N.I. Afanasieva; N.V. Sokerina; I.A. Perovskiy; B.M. Galiullin; V.P. Morozov; A.A. Eskin (Учёные записки Казанского университета: Серия Естественные науки)
The Mezino-Lapshinovka section is constituted by the Upper Cretaceous carbonate clayey siliceous succession. It has been studied by XRD, SEM, microprobe, and geochemical analyses in order to reconstruct the main geologic events that influenced the formation of gaizes in the NE Peri-Tethys. A new scenario for their formation proposes that open-ocean siliceous ooze might have been delivered to the active subduction zone of the African-Arabian plate and then deposited in the shallow basin of NE Peri-Tethys. The bentonite interbeds were probably formed due to diagenetic alteration of the volcanic ash. It has been suggested that the sea water during the Santonian- Campanian was characterized by the oxic conditions, while there were two short episodes of anoxia or so-called anoxic non-sulfidic conditions. The early Santonian anoxic episode can be linked to the global anoxic event OAE 3 in the NE Peri-Tethys. The Campanian Mn anomaly coupled with the simultaneous increase in δ13C is considered to be a manifestation the Campanian eustatic rise.